Dynamics of one-dimensional electron bunch with the rectangular profile of density, injected into plasma - Anisimov, I.O.; Tolochkevich, Y.M. (Вопросы атомной науки и техники, 2009)
Dynamics of electron bunch with initially rectangular density profile injected into plasma was studied for 1D model using PIC method. Dependencies of maximal beam density and maximal amplitude of wake wave field upon the model parameters (plasma density and temperature, beam density, velocity and duration) were obtained and interpreted. Deformation index as a qualitative characteristic of deformation of the bunch initial density profile is proposed, its dependencies on the model parameters were studied.